Forging Nonprofit Accounting Principles–An Update. - Weinstein, Edward A. (The Accounting Review, 1980)
ABSTRACT: This article continues the discussion which appeared in the October, 1978 issue on the factors which have influenced the AICPA's Subcommittee on Nonprofit Organizations in the fashioning of its Statement of Position 78-10. The author, who was a member of the Subcommittee, presents his view of the reasons why the Subcommittee arrived at several of its more salient conclusions.